2023
DOI: 10.1021/acs.nanolett.2c04404
|View full text |Cite
|
Sign up to set email alerts
|

First Superferromagnetic Remanence Characterization and Scan Optimization for Super-Resolution Magnetic Particle Imaging

Abstract: Magnetic particle imaging (MPI) is a sensitive, highcontrast tracer modality that images superparamagnetic iron oxide nanoparticles, enabling radiation-free theranostic imaging. MPI resolution is currently limited by scanner and particle constraints. Recent tracers have experimentally shown 10× resolution and signal improvements with dramatically sharper M−H curves. Experiments show a dependence on interparticle interactions, conforming to literature definitions of superferromagnetism. We thus call our tracers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…After that, Fung et al in 2023 developed new optimized MPI scan trajectories, i.e., Single-Pass-and-Raster that work better with the new class of MPI tracers known as superferromagnetic iron oxide nanoparticles (SFMIOs), enabling MPI scanners to more efficiently harness the order-of-magnitude resolution and sensitivity improvements of these nanoparticles compared to traditional SPIONs. 73 Finally, Nomura et al most recently presented an MPI capable of scanning humans, and they were possible to scale up the bore size diameter to 300 mm. 74 The evolution of MPI technology developments, instrumental advances, and applications over the past two decades have been summarized in Fig.…”
Section: Mpi Instrumentation and Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…After that, Fung et al in 2023 developed new optimized MPI scan trajectories, i.e., Single-Pass-and-Raster that work better with the new class of MPI tracers known as superferromagnetic iron oxide nanoparticles (SFMIOs), enabling MPI scanners to more efficiently harness the order-of-magnitude resolution and sensitivity improvements of these nanoparticles compared to traditional SPIONs. 73 Finally, Nomura et al most recently presented an MPI capable of scanning humans, and they were possible to scale up the bore size diameter to 300 mm. 74 The evolution of MPI technology developments, instrumental advances, and applications over the past two decades have been summarized in Fig.…”
Section: Mpi Instrumentation and Hardwarementioning
confidence: 99%
“…97 Recently, a study at UC Berkeley has shown that by allowing SPIONs to have strong interparticle interactions within a linear chain, the originally superparamagnetic behav-ior switches to superferromagnetism, and coercivity is observed. 73,96,[98][99][100] Most importantly, for MPI, when the coercivity threshold is reached, there is an extremely rapid magnetization reversal propagating through the entire linear chain giving effectively a very large change in magnetization over a very small change in applied field H (near-perfect dM/dH value that is ideal for MPI). These chains formed by SPIONs with strong inter-particle interactions are called superferromagnetic iron oxide nanoparticle chains (SFMIOs), and they exhibit non-zero coercivities and low saturation fields like ferromagnetic materials.…”
Section: Superferromagnetic Iron Oxide Nanoparticle Chains (Sfmios) A...mentioning
confidence: 99%
“…MPI has been used for cancer detection , and has been used to track engineered EVs to primary tumors in animal models. In addition to this, other applications of MPI have included vascular imaging, inflammation, , therapeutic studies , and cell tracking. Further, groups are working toward improved nanoparticles tailored for MPI, improvements in MPI hardware and acquisition , and image analysis. , Other imaging methods such as in vivo bioluminescence imaging (BLI) can be used as a complementary imaging modality in rodent models to associate or correlate MPI signals with other biological processes such as sites of metastatic lesions …”
Section: Introductionmentioning
confidence: 99%
“… 1 This allows the measurement of cerebral blood volumes within the brain for neuroimaging 5–7 or tracking CAR-T cells for cancer therapy. 8 Recent developments in MPI tracers suggest an order of magnitude improvement may be on the horizon, 9 but for these gains to manifest, it will require continued development of the particles with instruments that accurately reflect the magnetic fields produced in MPI. For this reason, magnetic particle spectrometers (MPSs) and magnetic particle relaxometers are often used, as they can produce the relevant field magnitudes and frequencies used in MPI but are far smaller, more cost effective, and provide more information about the SPION dynamics than full imagers.…”
Section: Introductionmentioning
confidence: 99%